The Partial Pressure of CO2 and Fluxes of CO2 in Semarang Bay, Indonesia - Max Rudolf Muskananfola; Nurul Latifah; Agus Hartoko; Sigit Febrianto; Johan Christian Winterwerp (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
The CO2 characteristics of the Semarang Bay system on the Northern coast of Java were investigated to understand the roles in carbon dioxide flux. The flux of carbon dioxide at the sea surface between seawater and atmosphere is essential for mitigating atmospheric CO2.  The aims of this study were to assess the variation of CO2 partial pressure seawater (pCO2sea) and CO2 flux and to analyse the water quality variable which has the larger influence on CO2 flux in the waters of Semarang Bay. The variables in this study were temperature, pH, salinity, and DO. Different methods were adopted in the analysis of water samples: spectrophotometric to measure chlorophyll-a and phosphate and titration method to measure Total Alkalinity (TA) and Dissolved Inorganic Carbon (DIC). A CO2 meter was used to measure the CO2atm. The lowest CO2 flux value was (1.86 mmol CO2 m-2 day-1) during the morning period while the pCO2sea reached 461.04 μatm and CO2 flux 83.79 mmol CO2 m-2 day-1 at night. At noon time, with increased temperature, pCO2sea was 461.04 μatm, and CO2 flux was 83.79 mmol CO2 m-2 day-1. The high concentration of chlorophyll-a ranged between 3.55–4.11 mg.L-1.  This chlorophyll-a concentration has a negative correlation with CO2 flux, and it was found that TA and DIC concentrations have no relationship with CO2 flux. Based on PCA analysis, it was found that the variability of CO2 flux in Semarang Bay is influenced by the variability of pCO2sea, sea surface temperature and kwa (affected by wind speed).